BAHAN ORGANIK TERLARUT DALAM AIR LAUT - Santoso, Arif Dwi (Jurnal Rekayasa Lingkungan)
Seawater contains high amounts of organic material and ions causing high salinity.The distribution of nutrients in the ocean is determined by ocean circulation, biological processes of uptake and mineralization, and subsequent regeneration of nutrients by migration of animals and by supply from the land.Topic related to sea water is important to discuss and to be a challenging with many researchers in Indonesia. In this paper, organic mater from sea water was learned in detail. The information contained of formulation history, justifi cation, distribution, advantages, and method of measure, type and effect to environment.Keywords: organic material, sea water, dissolved